O-004 Analysis of Chromatin and Transcriptional Profiles in Crohn's Disease Reveals Molecular Subclasses and Highlights Functional Regulatory Regions Implicated in Disease. (March 2016) - Weiser, Matthew; Sheikh, Shehzad; Kochar, Bharati; Gipson, Gregory; Herfarth, Hans; Sartor, Ryan; McGovern, Dermot; Rahbar, Reza; Sadiq, Timothy; Furey, Terrence; Koruda, Mark; Robinson, Adam
Abstract : Background: Crohn's disease (CD) is a chronic inflammatory disease of the gastrointestinal tract, characterized by an inappropriate immune response to the enteric microbiota. Chromatin based assays have successfully identified cell type and disease-specific regions of DNA accessibility, and have been linked to differential transcription of target genes, but this approach has yet to be explored in CD. In this study we performed formaldehyde-assisted isolation of regulatory elements (FAIRE-seq) to identify nucleosome-depleted regions associated with regulatory elements, and RNA-seq to quantify expression, to characterize disease-relevant changes in chromatin and establish links to putative target genes. Methods: Mucosal Biopsies for 21 CD and 12 non-IBD individuals were taken from macroscopically uninflamed portions of the ascending colon at time of surgery. We performed FAIRE-seq and RNA-seq on each tissue sample. Reads were aligned to personalized genomes constructed with genotypes assayed on the Illumina Immunochip platform. A genome-wide scan for differential regions and genes was performed using 2 sided t -tests on normalized read counts in 300bp regions (FAIRE-seq) and RPKM (RNA-seq). Results: RNA-seq data analysis across all samples identified 2 distinct classes of patients associated with epithelial cell lipid transport (class I, n = 10, CD; n = 1, non-IBD) and maintenance of cellular and luminal pH (class II, n = 11, CD, n = 11, non-IBD). To unravel potential gene regulatory mechanisms we analyzed chromatin profiles using FAIRE-seq and histone annotations using tissue specific ChIP-seq data sets. Class I patients showed increased accessibility at distal sites marked for enhancer activity in small intestine, and reduced accessibility at sites marked as enhancers in colon, suggesting 2 distinct regulatory programs driving the expression of differential genes. This pattern was reversed in class II samples. In an analysis restricting to class II, which was characterized by normal colon enhancer activity, we found regulatory regions specific to CD and non-IBD, respectively, as well as 51 and 507 genes upregulated in the respective cohorts. Top ontologies of genes upregulated in CD included host response to bacteria and immune response. Differential regulatory genes were enriched near TSSs of differentially expressed genes, implying putative causal effect. In an integrative analysis, we identified 72 regulatory regions that associate with both disease status and expression of nearby genes. A retrospective analysis of patients in class I and II revealed that the majority of patients (10/11) in class I required post-operative anti-TNF therapy for disease recurrence compared to only 1/11 CD patients in the class II group. Conclusions: We used chromatin status as a novel marker of disease in Crohn's. We identified a subset of CD patients that are characterized at the chromatin level in the colon by enrichment of enhancer marks specific to small intestine, and loss of enhancer activity specific to colon. Among individuals with enhancer activity indicative of normal colon, we integrated data from well-described transcriptional markers with novel chromatin variables to identify molecular associations and interactions that affect disease predisposition. Despite small patient numbers we were able to use chromatin profiles to identify patients that required post-operative management with anti-TNF agents.